A method for preparing a prussian blue positive electrode dual-response separator
Patent Information
- Application Number
- CN202611274952.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-09
AI Technical Summary
正极侧金属溶出影响隔膜捕获能力,隔膜捕获能力下降影响Na离子通量,负极侧金属沉积诱发副反应和气体生成,气体和压力变化又影响电芯厚度、界面接触和模组安全
(1)建立了正极溶出、隔膜捕获、Na离子传输和产气抑制之间的连续计算关系
Smart Images

Figure REF-OBJ-1787291675277-000001 
Figure REF-OBJ-1787291675277-000002 
Figure REF-OBJ-1787291675277-000003
Abstract
Description
Technical Field
[0001] This invention relates to the fields of sodium-ion battery materials, electrode manufacturing, cell assembly and operation management, and in particular to a method for preparing a Prussian blue positive electrode dual-response separator. Background Technology
[0002] Prussian blue analogue cathodes possess advantages such as low resource cost, open Na ion diffusion channels, low synthesis temperature, and high structural tunability, making them a promising cathode material for engineering applications in sodium-ion batteries. However, these materials are highly sensitive to water of crystallization, vacancy defects, surface residual salts, and high-voltage cycling. Under the influence of moisture, vacancies, residual sodium salts, or electrolyte side reactions, metal elements such as Fe, Mn, and Ni on the cathode side may enter the electrolyte in ionic form. After passing through the separator, the dissolved metal ions may be reduced and deposited on the surface of the hard carbon anode, or catalyze the continuous decomposition of the electrolyte, causing abnormal thickening of the SEI, resulting in increased internal resistance, reversible sodium loss, gas generation, and soft pack expansion.
[0003] Existing membrane modification schemes mostly focus on improving ceramic heat resistance, wettability, puncture strength, or flame retardancy, which can improve the basic safety performance of the membrane. However, they typically do not consider the metal dissolution behavior of Prussian blue analog cathodes as input for membrane design. Existing Prussian blue analog cathode material modification schemes often emphasize low-defect synthesis, surface coating, particle size control, or lattice water reduction, which can slow down degradation at the cathode material end. However, they lack a continuous calculation relationship with metal trapping, Na ion transport, and negative electrode side reaction suppression at the membrane end.
[0004] Existing publicly available information includes ceramic diaphragms, functionally coated diaphragms, metal ion adsorbents, flame-retardant diaphragms, and PBA cathode modification schemes. However, most of these schemes rely on a single material, a single structure, or a single process step. Materials research can explain the impact of vacancies, water, residual salts, electrolyte side reactions, and metal dissolution on cycle stability. It can also explain that CO2, H2, CO, and hydrocarbon gases may originate from positive and negative electrode interface reactions, electrolyte decomposition, and impurity water reactions. However, when these mechanistic test results are directly applied to engineering sites, there is still a lack of means to connect data entry, parameter calibration, calculation sequence, and output actions.
[0005] In actual production and operation, the failure of Prussian blue analogue cathode cells is progressively propagated along the material, electrode, cell, and module stages. Metal leaching from the cathode side affects the membrane's trapping capacity, which in turn affects the Na ion flux. Metal deposition on the anode side induces side reactions and gas generation, and changes in gas and pressure affect cell thickness, interface contact, and module safety. Providing only a fixed membrane formulation, coating thickness, or operating threshold is insufficient to accommodate batch-to-batch material variations, environmental fluctuations, and changes in operating conditions.
[0006] Therefore, there is an urgent need for a method that can establish a continuous calculation relationship between metal leaching flux, diaphragm capture capacity, Na ion flux loss, local acid-base buffering capacity and gas generation rate, and dynamically determine the diaphragm functional coating thickness, capture site density, buffer component dosage, process window and operation adjustment based on the calculation results. Summary of the Invention
[0007] To overcome the problems of Fe, Mn, Ni and other metal ion dissolution, transmembrane migration, negative electrode deposition and soft pack gas expansion that occur in the preparation, formation, cycling, storage and module operation of Prussian blue analog cathode sodium-ion batteries in the prior art, as well as the lack of continuous calculation relationship between the existing separator modification scheme and the cathode material modification scheme, this invention provides a method for preparing a Prussian blue cathode dual-response separator.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a Prussian blue positive electrode dual-response membrane includes the following steps: Collect material testing data, membrane structure data, cell operation data, and process equipment data for Prussian blue analogue cathode sodium ion cells. The data includes one or more of the following: cell voltage, current, temperature, positive electrode side metal ion concentration, membrane buffer component concentration, electrolyte inhibition component concentration, membrane functional coating thickness, porosity, tortuosity, pressure, thickness, impedance, and gas analysis results. The membrane state parameters are constructed, including the amount of metal ions captured in the functional layer on the positive electrode side of the membrane, the concentration of metal ions on the negative electrode side, the effective flux of Na ions through the membrane, the local buffer index of the membrane near the negative electrode side pores and interface region, and the membrane lifetime index. The metal leaching flux on the positive electrode side is calculated based on the concentration of metal ions on the positive electrode side, the cell voltage, and the concentration of the suppressing component in the electrolyte. The concentration of free metal ions in the membrane channels is calculated based on the metal dissolution flux on the positive electrode side, the effective volume of the membrane channels, and the membrane capture capacity. The metal ion capture capacity of the diaphragm is updated based on the concentration of free metal ions in the pores of the diaphragm, the maximum capture capacity, the adsorption rate coefficient, and the desorption rate coefficient. The capture site occupancy rate, remaining capture rate, and metal ion penetration ratio are calculated based on the metal ion capture amount and maximum capture capacity of the diaphragm, and the metal ion concentration on the negative electrode side is updated accordingly. The effective diffusion coefficient of Na ions was calculated based on the occupancy rate of the capture sites, the porosity of the membrane, and the tortuosity, and the effective flux of Na ions through the membrane was further calculated. The local buffer index is calculated based on the concentration of the buffer component and the equivalent concentration of the acidic byproduct, and the basic gas production rate is calculated based on the concentration of metal ions on the negative electrode side, the concentration of reactive components in the electrolyte, and the temperature. When the capture site occupancy rate and the local buffer index meet the preset dual threshold conditions, the basic gas production rate is amplified and corrected to obtain the dual-response corrected gas production rate. The membrane lifetime index is calculated based on the remaining capture rate, effective Na ion flux, and dual-response corrected gas generation rate. The membrane functional coating thickness, capture component ratio, buffer component ratio, coating parameters, formation parameters, or cell operating parameters are output based on the membrane lifetime index and Na ion flux retention rate. Prepare or adjust a dual-response membrane according to the output results. The dual-response membrane includes a metal ion capture and local buffering functional layer on the positive electrode side, an intermediate Na ion transport layer, and a side reaction suppression layer on the negative electrode side.
[0009] As a preferred technical solution, the membrane state quantity is written as:
[0010] in, This represents the diaphragm state vector during the k-th sampling period or process stage. This represents the amount of metal ions captured in the functional layer on the positive electrode side of the separator. The concentration of metal ions reaching the negative electrode side; This represents the effective flux of Na ions through the membrane. The local buffering index of the diaphragm near the negative electrode side pores and interface region; This refers to the diaphragm life index. The membrane state variables are updated periodically in the order of positive electrode dissolution, pore free metal accumulation, membrane capture, negative electrode side metal arrival, Na ion transport, local buffering, gas generation correction, and lifetime determination. Each state variable is derived recursively from the current input and the state variable of the previous cycle.
[0011] As a preferred technical solution, the metal leaching flux on the positive electrode side is calculated using the following formula:
[0012] in, The dissolution flux of metal ions from the positive electrode side into the electrolyte during the k-th period; This is the coefficient for the metal dissolution rate; The concentration of soluble metal ions on the positive electrode side; Voltage sensitivity coefficient; This represents the cell voltage or positive electrode relative reference potential in the kth cycle. Reference voltage; The coefficient representing the influence of the inhibitory component or complexing component on metal dissolution; The concentration of effective components in the electrolyte that can participate in inhibiting metal dissolution or stabilizing complexation; When the inhibitory component in the electrolyte and the buffering component in the membrane come from the same buffer or complexing material, the conversion is performed according to the following formula:
[0013] in, The effective proportion of buffer or complexing components entering the electrolyte and participating in the dissolution inhibition effect on the positive electrode side, with a value ranging from 0 to 1; This refers to the effective concentration of the buffer component in the diaphragm functional coating.
[0014] As a preferred technical solution, the concentration of free metal ions in the membrane channels is calculated using the following formula:
[0015] in, The concentration of free metal ions in the positive electrode side channel of the diaphragm during the kth period; For projection operators; This represents the upper limit of the metal ion concentration within the diaphragm pores. This represents the concentration of free metal ions within the diaphragm pores in the previous cycle. This refers to the effective electrolyte volume within the diaphragm pores. This represents the metal leaching flux; This represents the effective contact area between the positive electrode and the diaphragm. This refers to the sampling period or process stage time. For the quality of the diaphragm functional coating; and These represent the metal capture amounts for the current period and the previous period, respectively. The projection operator is used to limit the calculated values of the model to a physical range that is measurable, manufacturable, or operable for Prussian blue analog sodium-ion batteries. The upper and lower limits are determined by the failure boundary of the same system battery, the equipment processing capability, and the safe operating window.
[0016] As a preferred technical solution, the metal ion capture capacity of the membrane is updated according to the following formula:
[0017] in, For the diaphragm capture amount in the next cycle; This represents the current cycle diaphragm capture amount. Maximum capture capacity; The adsorption rate coefficient of metal ions; This represents the concentration of free metal ions within the membrane pores. This is the desorption or deactivation rate coefficient; When Fe, Mn, and Ni metal ions are present simultaneously in the Prussian blue analog cathode, the... and Labeled separately according to the type of metal, and weighted according to the concentration ratio of each metal ion in the membrane channels:
[0018] in, Indicates Fe, Mn, or Ni; Let be the molar proportion of the i-th type of metal ion in the total amount of free metal ions within the membrane channel, and its value ranges from 0 to 1, and satisfies the following conditions: ; and , respectively, are the adsorption rate coefficient and desorption rate coefficient of the i-th type of metal ion.
[0019] As a preferred technical solution, the capture site occupancy rate, remaining capture rate, metal ion penetration ratio, and negative electrode side metal ion concentration are calculated using the following formulas:
[0020]
[0021]
[0022]
[0023] in, The occupancy rate of the diaphragm capture sites in the kth cycle; The remaining capture rate of the diaphragm in the k-th cycle; The penetration ratio of metal ions in the kth period; The remaining capture capacity has a suppressive effect on metal penetration. This represents the concentration of metal ions on the negative electrode side in the next cycle. This represents the concentration of metal ions on the negative electrode side during the current cycle. This represents the upper limit of metal concentration on the negative electrode side. This is a correction factor for transmembrane migration; This refers to the effective volume of the electrolyte. It represents the rate coefficient for metal deposition, consumption, or fixation on the negative electrode side.
[0024] As a preferred technical solution, the effective diffusion coefficient of Na ions and the effective flux of Na ions are calculated according to the following formulas:
[0025]
[0026] in, The effective diffusion coefficient of Na ions in the kth period; The reference diffusion coefficient; The porosity of the diaphragm; Porosity index; The degree of diaphragm tortuosity; The coefficient representing the influence of capture site occupancy on Na ion transport resistance; This refers to the occupancy rate of the septum capture sites. This represents the effective flux of Na ions through the membrane. The difference in Na ion concentration across the membrane; For the effective transmission thickness of the diaphragm; The transference number of the Na ion; Let be the current in the k-th period; It is Faraday's constant; The effective area of the electrode; in, Used to calculate the additional effects of metal ion trapping on the effective cross-sectional area of the pores and the Na ion transport path.
[0027] As a preferred technical solution, the local buffer index, the basic gas production rate, and the dual-response corrected gas production rate are calculated using the following formulas:
[0028]
[0029]
[0030] in, The local buffering index of the diaphragm near the negative electrode side pores and interface region; This is the buffer response steepness factor; This represents the effective concentration of the buffer component. It refers to the equivalent concentration of acidic byproducts, HF-type byproducts, or localized acidity. The rate of formation of basic gases; This is the rate coefficient for gas production reaction; The concentration of reactive components in the electrolyte; This is the apparent activation energy of the gas-producing reaction; It is the gas constant; The temperature of the kth period; The gas generation rate is the corrected rate after the dual response. The remaining capture capacity has a suppressive effect on gas production. The local buffering capacity has a suppressive effect on gas production. The gas generation amplification factor is the result of the combined effects of high site occupancy and insufficient buffering. Among them, the A dual-threshold triggering rule is adopted, when the capture site occupancy rate Or local buffer index At that time, take ;when and hour, Take the value according to the calibration value.
[0031] As a preferred technical solution, in the dual-response membrane, the solid components of the positive electrode side metal ion capture and local buffering functional layer are as follows by mass: 45 parts of amino-functionalized mesoporous silica, 20 parts of nano-magnesium phosphate, 15 parts of polyvinylidene fluoride, and 20 parts of mesoporous alumina. The amino-functionalized mesoporous silica has an average particle size of 100–300 nm and a specific surface area of 200–500 m². 2 / g, with a surface amino content of 0.5–1.5 mmol / g; The average particle size of the nano-magnesium phosphate is 50–150 nm. The membrane life index and the recommended coating thickness for the next stage are calculated using the following formulas:
[0032]
[0033] in, This refers to the diaphragm life index. , , These are the weighting coefficients for the remaining capture rate, Na ion flux, and gas production inhibition, respectively, and they satisfy the following conditions: ; This represents the initial Na ion flux or the Na ion flux of the control membrane. The reference gas production rate is for a normal diaphragm or in its initial state. Recommended coating thickness for the next stage; This represents the current coating thickness. and These are the minimum and maximum functional coating thicknesses, respectively. Increase the step size factor for thicknesses when the life index is insufficient; This is the thickness correction coefficient when the Na ion flux is insufficient. This is the lower limit of the diaphragm life index; This represents the lower limit of Na ion flux retention rate. The Na ion flux retention rate; when When the controller increases the slit gap of the coating head, decreases the coating speed, increases the solid content of the slurry, or increases the coating amount per unit area; when At the same time, the controller reduces the slit gap of the coating head, increases the coating speed, reduces the solid content of the slurry, or increases the proportion of pore-forming components; When the measured unit cycle gas production increment of the battery cell Exceeding the benchmark unit cycle gas production increment 5%, or the dual-response corrected gas production rate over three consecutive sampling periods. All are not lower than the first gas production threshold. At that time, the processor sends an operation correction command to the formation device, capacity grading device, or BMS; among them, for a 5Ah Prussian blue analog cathode soft-pack sodium-ion battery cell, the first gas generation threshold is... for mol / s, second gas production threshold for mol / s, third gas production threshold for mol / s; When the unit cycle gas production increment exceeds 5% of the baseline unit cycle gas production increment and the dual-response corrected gas production rate Less than the first gas production threshold , or when When the charging voltage limit is reached, the upper limit voltage will be lowered by 0.05V; when When the charging voltage limit is reached, the upper limit voltage will be lowered by 0.10V; when When this occurs, the upper limit voltage for charging will be lowered by 0.15V; the operation correction instruction also includes one or more of the following: reducing the charging rate, shortening the high voltage holding time, or extending the formation and exhaust time.
[0034] The present invention also discloses a dual-response diaphragm preparation control system for performing the above method, comprising a data acquisition module, a state calculation module, a parameter output module, an execution control module and a parameter backfilling module; The data acquisition module is used to collect one or more of the following: cell voltage, current, temperature, positive electrode side metal ion concentration, buffer component concentration, inhibitory component concentration, separator coating thickness, porosity, tortuosity, pressure, thickness, impedance, and gas analysis results. The state calculation module is used to calculate the positive electrode side metal dissolution flux, free metal ion concentration in the membrane channel, membrane capture amount, capture site occupancy rate, remaining capture rate, metal ion penetration ratio, negative electrode side metal ion concentration, Na ion effective diffusion coefficient, Na ion effective flux, local buffer index, basic gas production rate, dual-response corrected gas production rate and membrane lifetime index. The parameter output module is used to output the membrane functional coating thickness, capture component ratio, buffer component ratio, coating parameters, formation parameters, or cell operating parameters based on the membrane lifetime index and Na ion flux retention rate. The execution control module is used to control the coating equipment, drying equipment, calendering equipment, formation equipment, capacity separation equipment, or BMS to perform corresponding actions based on the output results of the parameter output module; when the output... At the same time, the controller adjusts the slit gap and coating speed through the coating equipment, adjusts the drying temperature through the drying equipment, and adjusts the calendering pressure through the calendering equipment; The parameter backfilling module is used to backfill the measured capacity, impedance, pressure, thickness, gas generation, and metal deposition results into the parameter table, and to correct the model parameters.
[0035] Compared with the prior art, the advantages of the present invention are: (1) A continuous calculation relationship was established between positive electrode dissolution, membrane trapping, Na ion transport and gas generation suppression. This invention incorporates the metal dissolution flux, membrane capture capacity, Na ion flux loss, local acid-base buffering capacity, and gas generation rate in Prussian blue analog cathode cells into the same calculation framework, and writes the measurable input, intermediate state, state recursion, window determination, and output action into the same executable technical process. (2) It can adapt to batch differences in materials, environmental fluctuations and changes in working conditions. The model of this invention determines the remaining capture site, buffer capacity, membrane lifetime index and coating thickness suggestions based on the metal dissolution flux on the positive electrode side, membrane adsorption capacity, Na ion flux loss and gas production rate, and outputs a dynamic executable parameter window. This overcomes the shortcomings of fixed membrane formulation, fixed coating thickness or fixed operating threshold that cannot adapt to material batch differences, environmental fluctuations and changes in operating conditions. (3) It can cover the entire stages of research and development, production and operation. This invention can be used for membrane structure screening during the R&D stage, for process release and rework judgment during the production stage, and for risk warning and parameter correction in BMS or EMS during the operation stage. (4) The gas production amplification factor adopts a dual threshold triggering rule, which can identify the risk of gas expansion when both metal trapping capacity and local buffering capacity are insufficient. when and At that time, the gas production amplification factor Participate in calculation; when or hour, =0. This rule can identify the risk of gas expansion when both reduced metal trapping capacity and insufficient local buffering capacity occur simultaneously; (5) It can maintain the Na ion flux while reducing metal penetration, gas generation and thickness growth. The test results show that after 500 cycles, the metal arrival rate on the negative electrode side is about one-fifth to one-third of that of ordinary diaphragm groups, the increase in soft pack thickness is controlled within about 3%, the capacity retention rate is maintained in the range of about 88% to 91% after 500 cycles, and the Na ion flux retention rate is maintained above about 90%. The comparative results show that the dual-response membrane, by simultaneously setting a metal trapping and local buffering functional layer on the positive electrode side, an intermediate Na ion transport layer, and a side reaction suppression layer on the negative electrode side, can reduce metal penetration, gas generation, and thickness growth while maintaining Na ion flux. Detailed Implementation
[0036] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.
[0037] I. Model Building and Parameter Acquisition (1) Model state variables, input variables and output variables In Prussian blue analogue cathode cells, metal dissolution, membrane trapping, Na ion migration, and anode gas generation exhibit a continuous transmission relationship. After metal ions enter the electrolyte from the positive electrode side, they enter the membrane channels and are trapped by the functional coating. As the trapping sites are gradually occupied, they alter the membrane channel environment and the Na ion transport resistance. When some metal ions pass through the membrane and reach the anode side, they promote electrolyte side reactions and abnormal SEI growth, leading to gas generation and increased pouch thickness.
[0038] To ensure that the above process can be updated in the same calculation order, the operating state of the diaphragm in the kth cycle is written as:
[0039] in, This represents the diaphragm state vector during the k-th sampling period or process stage. This represents the amount of metal ions captured in the functional layer on the positive electrode side of the membrane, expressed in mol / g, with a value ranging from 0 to... ; The concentration of metal ions reaching the negative electrode side, expressed in mol / L, ranging from 0 to... mol / L; This represents the effective flux of Na ions through the membrane, expressed in mol / (cm). 2 ·s), the range of values is to mol / (cm 2 ·s); It is a dimensionless local buffer index for the diaphragm near the negative electrode side pores and interface region, and its value ranges from 0 to 1. It is a diaphragm life index, dimensionless, with a value ranging from 0 to 1.
[0040] The state vector is set according to the order of migration and interaction of metal ions in the cell. Corresponding to the metal trapping capability of the functional layer on the positive electrode side of the separator, This addresses the risk of metal ions accumulating on the negative electrode side after penetrating the membrane. Corresponding to the Na ion transport performance in the membrane, This corresponds to the local buffering capacity of the diaphragm near the negative electrode side pores and interface region. This corresponds to the available state of the diaphragm calculated from the combined effects of capture, penetration, transport, and gas generation. All of these states are recursively derived from the current input and the state of the previous cycle, and are used to describe the actual operating state of the diaphragm in the cell during the k-th cycle.
[0041] The model input is written as:
[0042] in, This is the input vector for the kth sampling period or process stage; This is the cell voltage or positive terminal relative to the reference potential, measured in volts (V), typically ranging from 1.5 to 4.3V. This is the charging and discharging current, measured in amperes (A). Its range is determined by the cell capacity and rate program. This refers to the cell temperature or process temperature, measured in K, with a typical range of 253 to 353 K. This represents the concentration of metal ions on the positive electrode side, expressed in mol / L, with a range of values of [value missing]. to mol / L; The effective concentration of the buffer component in the diaphragm functional coating is expressed in mol / L, and its value range is [value range missing]. Up to 1 mol / L; It represents the concentration of the effective component in the electrolyte that can participate in the inhibition of metal dissolution or the stabilization of complexation, expressed in mol / L, with a value range of 0 to 1 mol / L; The thickness of the diaphragm functional coating is expressed in μm and ranges from 0.2 to 8 μm.
[0043] in, It is mainly used to calculate the local buffer index of the diaphragm near the negative electrode side pores and interface region. It is mainly used to calculate the metal dissolution flux on the positive electrode side. Both can originate from the same functional component or different components. When both originate from the same buffer or complexing material, they can be converted using the following formula:
[0044] in, The effective proportion of buffer or complexing components entering the electrolyte and participating in the dissolution inhibition effect on the positive electrode side is dimensionless and ranges from 0 to 1. and The meaning is the same as before.
[0045] The model output is written as:
[0046] in, Output vectors for the model; The metal capture rate is dimensionless and ranges from 0 to 1. The Na ion flux retention rate is dimensionless and ranges from 0 to 1. The gas production reduction rate is dimensionless and ranges from 0 to 1. It is a diaphragm life index, dimensionless, with a value range from 0 to 1; The recommended coating thickness for the next stage is in μm, ranging from 0.2 to 8 μm.
[0047] Through the above input, state, and output settings, the model can process cathode material testing results, separator structural parameters, cell operating data, and final process actions in the same calculation sequence. Input data can come from offline testing or online sampling; output results can be used as separator preparation parameters or as a basis for adjustments during cell formation, capacity testing, cycling, or operation management.
[0048] This model is updated cyclically in the following order: cathode dissolution, pore-bound free metal accumulation, membrane trapping, negative electrode metal arrival, Na ion transport, local buffering, gas generation correction, and lifetime determination. Each state variable is recursively derived from the current input and the state variables of the previous cycle, without employing a calculation method that uses the final lifetime exponent to reverse-correct preceding chemical states. This setting ensures that the model's running sequence aligns with the actual direction of metal ion migration and side reaction development in PBA cells.
[0049] Projection operator in this invention This is used to limit the calculated values of the model within the physical range that the PBA (Polymerized Element-Based Battery) soft-pack cell is measurable, manufacturable, or operable. Its upper and lower limits are determined by the failure boundaries of cells within the same system, equipment processing capabilities, and safe operating windows. For example, Limited to 0 to 1, Limited to 0.2 to 8 μm, Limited to 0 to .
[0050] (2) Model calculation method 1. Calculation of metal leaching flux on the positive electrode side Metal elements such as Fe, Mn, and Ni in the Prussian blue analogue cathode may enter the electrolyte under the influence of moisture, vacancy defects, surface residual salts, and high-voltage cycling. After leaving the cathode framework, metal ions will enter the membrane channels and migrate towards the anode side. Therefore, it is necessary to first calculate the metal dissolution flux per unit area and per unit time on the cathode side.
[0051] This invention introduces a voltage-driven term and a suppressor term into the calculation of metal dissolution. The voltage-driven term describes the accelerated dissolution caused by the enhanced oxidation side reactions on the cathode surface at high potentials, while the suppressor term describes the weakening effect of interfacial stabilizing components, complexing components, or additives in the electrolyte on the release of metal ions. The metal dissolution flux is calculated using the following formula:
[0052] in, This represents the dissolution flux of metal ions from the positive electrode side into the electrolyte during the k-th period, expressed in mol / (cm²). 2 ·s), the range of values is to mol / (cm 2 ·s); This is the metal dissolution rate coefficient, with units determined according to the formula's dimensions. The standard calibration range is [range missing]. to cm / s; This represents the concentration of soluble metal ions on the positive electrode side, expressed in mol / L, with a range of values of [value missing]. to mol / L; Voltage sensitivity coefficient, unit: V The value ranges from 0 to 10; This represents the cell voltage or positive electrode relative reference potential in the kth cycle, in V. This is a reference voltage, in volts (V), which can be set according to the cathode material system. The coefficient representing the effect of the inhibitory component or complexing component on metal dissolution, expressed in L / mol, with a value ranging from 0 to... L / mol; It represents the concentration of the effective component in the electrolyte that can participate in the inhibition of metal dissolution or the stabilization of complexation, expressed in mol / L, with a value ranging from 0 to 1 mol / L.
[0053] Equation (5) serves to convert the degree of instability on the positive electrode side into the design inlet for the diaphragm. If A higher value indicates that the positive electrode side of the membrane requires a higher metal capture capacity or a higher density of capture sites; if If the concentration is low, the coating thickness can be appropriately reduced to minimize the impact on Na ion flux.
[0054] In the PBA system, and It is determined by a combination of lattice water content, vacancy ratio, surface residual salt, and metal composition. For manganese-iron-based PBA with high water vacancies, and The value can be higher than that of the low-defect PBA system to reflect the accelerated metal dissolution induced by lattice water and vacancies. Therefore, the metal dissolution calculation in equation (5) does not use the voltage exponent alone, but incorporates the concentration of soluble metals on the positive electrode side of PBA, voltage sensitivity, and the concentration of suppressing components in the electrolyte.
[0055] 2. Calculation of free metal ion concentration within the diaphragm pores After metal ions enter the electrolyte from the positive electrode side, they do not immediately all reach the negative electrode side. Some remain in the membrane pores, while others are captured by the functional coating. To ensure that the membrane capture calculation has a clear entry point, this invention calculates the concentration of free metal ions in the membrane pores based on the dissolution flux on the positive electrode side, the effective volume of the membrane pores, and the capture amount in the previous cycle.
[0056] The concentration of free metal ions within the membrane pores is calculated using the following formula:
[0057] in, The concentration of free metal ions in the positive electrode side channel of the diaphragm during the kth period is expressed in mol / L and ranges from 0 to [value missing]. ; This represents the upper limit of metal ion concentration within the membrane pores, expressed in mol / L, with a range of values of [value missing]. to mol / L; This is a projection operator used to avoid calculating concentrations below 0 or exceeding a set upper limit; This represents the concentration of free metal ions in the membrane channels of the previous cycle, in mol / L. This represents the effective electrolyte volume within the diaphragm channels, expressed in liters (L). The value is calculated from the diaphragm porosity, thickness, and effective area. The metal leaching flux calculated by equation (5) is expressed in mol / (cm). 2 ·s); The effective contact area between the positive electrode and the diaphragm is expressed in cm². 2 ; The sampling period or process stage time is expressed in seconds (s). The mass of the diaphragm functional coating is expressed in grams. and These represent the metal capture amounts for the current period and the previous period, respectively, in mol / g.
[0058] Equation (6) is established based on the conservation relationship of metal ions within the pores. The concentration of free metal ions within the pores is determined by the metal ions remaining in the membrane pores from the previous cycle, the metal ions dissolved from the positive electrode side and entering the pores in the current cycle, and the metal ions newly captured by the functional coating. Through this equation, The data is updated from the positive electrode dissolution flux, membrane pore volume, and capture capacity, and used as input for subsequent adsorption recursion and negative electrode migration calculations.
[0059] 3. Recursive occupancy of septum capture sites The metal ion trapping sites in the coating on the positive electrode side of the separator can adsorb, complex, or immobilize ions such as Fe, Mn, and Ni. As cycling progresses, these trapping sites are gradually occupied, and the remaining trapping capacity decreases. If only the fixed adsorption capacity is used to evaluate the separator performance, it is difficult to determine the rate of functional layer degradation during long-term cycling. Therefore, this invention adopts a time-updated trapping capacity calculation method.
[0060] The capture process employs a kinetic model jointly controlled by adsorption and desorption. The adsorption term calculates the rate at which metal ions occupy the remaining capture sites, while the desorption term accounts for the release process following site instability, dissociation, or consumption by side reactions. The membrane capture capacity is updated using the following formula:
[0061] in, This represents the membrane capture amount for the next cycle, expressed in mol / g, and ranges from 0 to... ; This represents the membrane capture amount for the current cycle, expressed in mol / g. This is a projection operator used to limit the calculation results to 0 to... Within the range; The k-th period time interval is in seconds and its value is determined by the sampling period or process stage. This is the metal ion adsorption rate coefficient, with units determined according to the formula's dimensions. The standard calibration range is [range missing]. to ; The free metal ion concentration in the membrane pores calculated by equation (6) is expressed in mol / L and has a range of values of [value range missing]. to mol / L; The maximum capture capacity is expressed in mol / g and its range is [value missing]. to mol / g; This is the desorption or deactivation rate coefficient, measured in seconds. -1 The range of values is to s -1 .
[0062] Equation (7) transforms the diaphragm trapping capacity from a static material parameter into a state variable that changes with the progression of the cycle. The model is based on... and The proximity of the capture site determines whether it has entered a high-occupancy area, and provides advance suggestions on coating thickness, capture component ratio, or derating.
[0063] When Fe, Mn, Ni and other metal ions are present in the PBA cathode, the equation (7) is as follows: and It can be labeled separately according to the type of metal, and weighted according to the concentration ratio of each metal ion in the pore:
[0064] in, Indicates Fe, Mn, or Ni; Let be the molar proportion of the i-th type of metal ion in the total amount of free metal ions within the membrane channel, and its value ranges from 0 to 1, and satisfies the following conditions: ; is the adsorption rate coefficient of the i-th type of metal ion, and the unit is determined according to the formula dimensions; The desorption rate coefficient of the i-th type of metal ion is expressed in seconds. -1 This process allows the membrane capture recursion to distinguish the adsorption differences of Fe, Mn, and Ni ions, avoiding the mistreatment of different metal ions according to the same adsorption behavior.
[0065] 4. Calculation of capture site occupancy rate and metal arrival amount on the negative electrode side The membrane's capture capacity is limited. When capture sites are continuously occupied, the remaining capture capacity decreases, and more metal ions may pass through the membrane and enter the negative electrode side. These metal ions may be reduced and deposited on the hard carbon negative electrode surface, or catalyze the reduction and decomposition of the electrolyte, causing the SEI film to continuously thicken. To link the membrane's capture status with the risk of metal accumulation on the negative electrode side, this invention first calculates the capture site occupancy rate and the remaining capture rate:
[0066]
[0067] in, The occupancy rate of the diaphragm capture sites in the kth cycle is dimensionless and ranges from 0 to 1. The remaining capture rate of the diaphragm in the k-th cycle is dimensionless and ranges from 0 to 1. This represents the metal capture amount for the current cycle, expressed in mol / g. Maximum capture capacity, in mol / g; To prevent small quantities with a denominator of zero, the range of values is [range missing]. to mol / g.
[0068] To avoid misinterpreting an increase in the amount of metal ions already captured as a reduction in the risk of subsequent penetration, this invention uses the remaining capture rate to calculate the metal ion penetration ratio. A higher remaining capture rate indicates a lower proportion of metal ions penetrating the membrane; a higher capture site occupancy rate indicates a weaker ability of the membrane to continue intercepting metal ions. The metal ion penetration ratio is calculated using the following formula:
[0069] in, The penetration ratio of metal ions in the k-th period is dimensionless and ranges from 0 to 1. The residual capture capacity is the inhibition coefficient of metal penetration, which is dimensionless and ranges from 0 to 1. denoted as the residual capture rate of the diaphragm in the k-th cycle, dimensionless, and ranging from 0 to 1.
[0070] The concentration of metal ions on the negative electrode side is updated using the following formula:
[0071] in, This represents the concentration of metal ions on the negative electrode side in the next cycle, expressed in mol / L, ranging from 0 to... ; This represents the concentration of metal ions on the negative electrode side in the current cycle, in mol / L. This represents the upper limit of the metal concentration on the negative electrode side, expressed in mol / L. It can be taken as... mol / L or determined experimentally; For projection operators; The sampling period or process stage time is expressed in seconds (s). This is a dimensionless correction factor for transmembrane migration, ranging from 0 to 1. The effective contact area between the positive electrode and the diaphragm is expressed in cm². 2 The value is determined by the cell structure; The metal leaching flux obtained from equation (5) is expressed in mol / (cm³). 2 ·s); The metal ion penetration ratio obtained by equation (11); The effective volume of the electrolyte is expressed in liters (L). The negative electrode side metal deposition, consumption, or fixation rate coefficient, in seconds. -1 The range of values is to s -1 .
[0072] Equation (12) is used to connect the risks of positive electrode metal dissolution, membrane capture attenuation, and negative electrode side reactions. When At higher levels, The lower value indicates that the diaphragm still has good interception capability; when rise and When it decreases, Increased size raises the risk of metal accumulation on the negative electrode side.
[0073] 5. Calculation of the effective diffusion coefficient of Na ions While the functional coating of the diaphragm increases metal trapping capability, it may also alter pore connectivity, electrolyte wettability, and local ion migration resistance. If the coating is too thick or the trapping sites are too occupied, the resistance of Na ions through the diaphragm will increase, leading to a decrease in cell polarization and rate performance. Therefore, this invention incorporates a trapping site occupancy correction term into the effective diffusion coefficient, ensuring that the diaphragm design is simultaneously constrained by both metal trapping capability and Na ion transport capability.
[0074] After metal ions are captured by the functional coating, local occupancy, solvation structure changes, and a decrease in the effective cross-sectional area of the pores occur near the capture sites. This effect can be equivalent to an increase in the Na ion transport path or an increase in effective tortuosity. Therefore, this invention adds a capture site occupancy term to the traditional porosity-torsuosity correction relationship to describe the additional resistance of the metal capture process to Na ion transport.
[0075] The effective diffusion coefficient of Na ions is calculated using the following formula:
[0076] in, The effective diffusion coefficient of Na ions in the kth period is given in cm⁻¹. 2 / s, with a value range of to cm 2 / s; The reference diffusion coefficient is expressed in cm⁻¹. 2 / s, with a value range of to cm 2 / s; The membrane porosity is dimensionless and ranges from 0.25 to 0.75. Porosity index, dimensionless, with a value range of 1 to 4; The diaphragm tortuosity is dimensionless and ranges from 1 to 10. The coefficient representing the effect of capture site occupancy on Na ion transport resistance is dimensionless and ranges from 0 to 10. The occupancy rate of the diaphragm capture sites obtained by equation (9) is dimensionless and ranges from 0 to 1.
[0077] Equation (13) is used to control the transport side effects caused by the functionalization modification of the diaphragm. The model will not only increase the coating thickness based on the metal capture rate, but will also simultaneously check... Whether to enter the low diffusion region. When the effective diffusion coefficient is lower than the set window, the model outputs suggestions to reduce the coating thickness, increase the porosity, or adjust the coating particle size distribution.
[0078] 6. Calculation of Na ion migration flux The actual transport of Na ions through the membrane is influenced by both the concentration gradient and the current driving force. The diffusion coefficient alone cannot reflect the true ion migration capability of the cell under charge and discharge conditions; therefore, this invention further calculates the effective Na ion flux. This flux includes the diffusion term caused by the concentration gradient, as well as the migration term formed when current passes through the membrane.
[0079] The Na ion migration flux is calculated using the following formula:
[0080] in, The effective flux of Na ions through the membrane in the kth period is expressed in mol / (cm²). 2 ·s), the range of values is to mol / (cm 2 ·s); The effective diffusion coefficient obtained from equation (13) is expressed in cm. 2 / s; This represents the Na ion concentration difference across the membrane, expressed in mol / cm³. 3 The value is determined by the electrolyte concentration and polarization state; The effective transport thickness of the diaphragm is expressed in cm, and its value range is [value range missing]. to cm; is the Na ion transfer number, dimensionless, and ranges from 0 to 1; The current in the kth period is expressed in amperes (A). The value is Faraday's constant, taken as 96485 C / mol; The effective area of the electrode is expressed in cm². 2 .
[0081] Equation (14) is used to determine whether the functional coating affects normal charging and discharging. If The decrease is significant. Even with good metal capture, the model will limit further increases in coating thickness to avoid the risk of decreased rate performance, increased polarization, and localized sodium precipitation caused by diaphragm modification.
[0082] 7. Calculation of local acid-base buffer index Residual sodium salts, water of crystallization, electrolyte decomposition products, and negative electrode side reaction products in Prussian blue analog cathode materials can alter the local acid-base environment near the membrane. Local acid-base drift can affect metal ion stability, electrolyte decomposition pathways, and SEI membrane growth. To evaluate the stabilizing effect of buffer components in the membrane on the local environment, this invention establishes a local acid-base buffering index.
[0083] This index is calculated using an S-shaped function, which converts the difference between the effective concentration of the buffer component and the equivalent concentration of acidic byproducts into a state value between 0 and 1, facilitating subsequent gas production rate correction.
[0084] in, , is the local buffer index of the membrane near the negative electrode side pores and interface region in the k-th cycle, dimensionless, and ranging from 0 to 1; This is the buffer response steepness coefficient, expressed in L / mol, with a value ranging from 1 to... L / mol; The effective concentration of the buffer component is expressed in mol / L, and its value range is [value missing]. Up to 1 mol / L; This refers to the equivalent concentration of acidic byproducts, HF-type byproducts, or localized acidity, expressed in mol / L, with a range of values. Up to 1 mol / L.
[0085] Equation (15) transforms the buffer capacity into a computable state. When the value is close to 1, it indicates that the acid-base environment of the membrane near the negative electrode side pores and interface region is relatively stable. When the value is close to 0, it indicates insufficient buffer components, increasing the risk of electrolyte decomposition and gas generation. This state will continue to be included in the gas generation correction formula and participate in the membrane life assessment.
[0086] 8. Calculation of basic gas production rate on the negative electrode side Metal ions reaching the negative electrode side alter the side reaction pathways on the hard carbon negative electrode surface. Metal deposition sites may become active sites for electrolyte reduction and decomposition, leading to continuous SEI growth and the production of CO2, CO, H2, or hydrocarbon gases. The side reaction rate further accelerates with increasing temperature. To calculate the gas production trend before applying dual-response correction, this invention employs a basic gas production rate formula jointly controlled by concentration and temperature terms.
[0087] The basic gas production rate is calculated using the following formula:
[0088] in, The rate of formation of the fundamental gas in the kth period is expressed in mol / s and ranges from 0 to 6. mol / s; It is the gas production reaction rate coefficient, and its unit is determined according to the formula dimensions. It can be calibrated by gas analysis or pressure testing. This represents the concentration of metal ions on the negative electrode side, expressed in mol / L, and ranging from 0 to... mol / L; The concentration of the reactive components in the electrolyte is expressed in mol / L, and the range of values is [value missing]. Up to 2 mol / L; The apparent activation energy of the gas-producing reaction is expressed in J / mol, and its value ranges from [value missing]. to J / mol; The gas constant is taken as 8.314 J / (mol·K); The temperature of the k-th cycle is expressed in K, with a typical range of 253 to 353 K.
[0089] Equation (16) gives the basic gas production intensity of the negative electrode side reaction. The model can be obtained through... This study aims to determine the gas generation trend under conditions of high-temperature cycling, high-voltage storage, or increased metal penetration, and to provide a calculation basis for the design of buffer components and side reaction suppression layers in dual-response membranes.
[0090] 9. Calculation of Gas Production Rate with Dual Response Correction The basic gas production rate mainly reflects the effects of metal concentration on the negative electrode side, reactive components of the electrolyte, and temperature, without taking into account the regulatory role of the membrane functional layer on metal penetration and the local acid-base environment. The gas production control capability of the dual-response membrane comes from two aspects: the remaining trapping sites reduce the probability of further metal ion penetration, and the buffering components reduce acid-base drift in the negative electrode side channels and interface regions. When the trapping sites approach saturation and the buffering index decreases, both types of protective effects weaken simultaneously, and the gas production rate accelerates.
[0091] The gas production rate after the dual-response correction is calculated using the following formula:
[0092] in, The gas generation rate is the corrected rate for the two-response reaction, expressed in mol / s, and ranges from 0 to... mol / s; The basic gas generation rate obtained from equation (16) is expressed in mol / s. The residual capture capacity is the inhibition coefficient of gas production, which is dimensionless and ranges from 0 to 1. The remaining capture rate obtained by equation (10) is dimensionless and ranges from 0 to 1; The local buffering capacity is the inhibition coefficient of gas production, which is dimensionless and ranges from 0 to 1. The local buffer index obtained by equation (15) is dimensionless and ranges from 0 to 1. The gas generation amplification factor is a dimensionless factor that takes a value from 0 to 5, which is used to capture the combined effects of high site occupancy and insufficient buffering. The capture site occupancy rate obtained by equation (9) is dimensionless and ranges from 0 to 1.
[0093] In equation (17), Used to calculate the inhibitory effect of residual capture capacity on metal penetration gas generation. Used to calculate the inhibitory effect of local buffering capacity on the gas production from electrolyte side reactions. This formula is used to calculate the gas amplification effect when the capture sites are highly occupied and the buffering capacity is insufficient. It can be used to address the risk of gas expansion when both reduced capture capacity and insufficient buffering capacity of the diaphragm metal occur simultaneously.
[0094] Compared to using only linear superposition, equation (17) can reflect the risk amplification process when both functional layers decline simultaneously. When rise and When the rate decreases, it indicates that the capture sites are close to saturation and there is insufficient local buffering. The model will then transform this state into a higher corrected gas production rate, which will further affect the diaphragm lifetime index and subsequent process actions.
[0095] The gas generation amplification factor in equation (17) adopts a dual-threshold triggering rule. When the capture site occupancy rate Or local buffer index When this occurs, it indicates that the diaphragm still has the ability to intercept metal ions or provide local buffering capacity. The gas production scale-up term is not included in the calculation. and This indicates that the membrane capture sites are close to a high occupancy state and that the buffering capacity of the pores and interface region near the negative electrode is insufficient. Values are taken from the calibration values, and the gas production amplification term is included in the calculation. Through this dual-threshold rule, the model can identify the risk of gas expansion when both reduced metal trapping capacity and insufficient local buffering capacity occur simultaneously.
[0096] 10. Calculation of diaphragm life index Whether a diaphragm is suitable for continued use cannot be determined solely by its metal capture rate. If the capture rate is strong but the Na ion flux is significantly reduced, the cell will experience a decrease in rate capability and an increase in polarization. Conversely, if the Na ion flux is good but the gas generation rate is high, the expansion of the soft pack and deterioration of interfacial contact will still accelerate failure. Therefore, this invention combines the remaining capture rate, Na ion flux, and gas generation suppression effect into a diaphragm lifetime index for a unified assessment of the diaphragm's current condition.
[0097] The diaphragm life index is calculated using the following formula:
[0098] in, is the diaphragm lifetime index for the kth period, which is dimensionless and its value range is limited to 0 to 1 after projection; For projection operators; , , These are the weighting coefficients for residual capture rate, Na ion flux, and gas production inhibition, respectively. They are dimensionless, range from 0 to 1, and satisfy the following conditions: ; The remaining capture rate is obtained from equation (10); The Na ion flux obtained from equation (14) is expressed in mol / (cm²). 2 ·s); This represents the initial Na ion flux or the control membrane Na ion flux, in mol / (cm²). 2 ·s), the range of values is to mol / (cm 2 ·s); To prevent small quantities with a denominator of zero, the range of values is [range missing]. to mol / (cm 2 ·s); The corrected gas production rate obtained from equation (17) is expressed in mol / s. This is the baseline gas production rate under normal diaphragm or initial conditions, expressed in mol / s, and ranging from 0 to... mol / s; To prevent small quantities with a denominator of zero, the range of values is [range missing]. to mol / s.
[0099] The weighting coefficients are determined based on the cell's application scenario and failure control objectives. For cells prioritizing long cycle life, the weighting coefficients can be adjusted accordingly. , , To improve the impact of metal capture margin and gas generation suppression on lifespan determination; for cells with priority given to power performance, the following can be adopted. , , To improve the effect of Na ion flux retention rate; in a general evaluation scenario, the following can be taken: The weights can also be obtained by fitting data on cycle life, EIS impedance growth, gas generation, and pouch thickness growth.
[0100] Equation (18) is used to compress multiple failure factors into an executable decision quantity. At a higher level, it indicates that the diaphragm still has the ability to capture excess capacity, maintain flux, and suppress gas production; When the rate continues to decline, the model can output suggestions in advance for coating correction, process rework, formation parameter adjustment, or de-rate operation.
[0101] 11. Coating thickness and process output The model ultimately needs to be translated into executable actions during membrane fabrication or cell operation. If only metal concentration, gas generation rate, or lifetime index is output, manual judgment is still required on-site to adjust the process. Therefore, this invention incorporates lifetime index deviation and Na ion flux deviation into the coating thickness update formula to generate recommendations for the next stage of functional coating thickness.
[0102] When the membrane lifetime index falls below a set value, the thickness correction term increases to improve capture capacity and buffering ability; when the Na ion flux retention rate falls below a set value, the thickness correction term increases to prevent excessive coating thickness from hindering ion transport. Coating thickness is updated using the following formula:
[0103] in, Recommended coating thickness for the next stage, in μm, with a range of values. to ; This is a projection operator used to limit the coating thickness within an allowable range. The minimum functional coating thickness, in μm, ranges from 0.2 to 1 μm; The maximum functional coating thickness is expressed in μm and ranges from 4 to 8 μm. This represents the current coating thickness, in μm. The step size factor is increased for thicknesses that are insufficient for the lifetime index, with the unit being μm and the value ranging from 0 to 2 μm; This is the lower limit of the diaphragm life index, dimensionless, and ranges from 0.5 to 0.9. The membrane life index is obtained from equation (18); This is the thickness correction coefficient when the Na ion flux is insufficient, in μm, and its value ranges from 0 to 2 μm. The lower limit of Na ion flux retention rate is dimensionless and ranges from 0.7 to 0.95. The Na ion flux retention rate is calculated based on... calculate.
[0104] in, This can be obtained by calibrating the failure boundary of the same type of diaphragm in standard cycle testing. For example, under 25°C, 1C cycle conditions, when the cell EIS impedance increases to 120% of its initial value, the pouch thickness increases by 3%, or the capacity retention rate decreases to 80%, the corresponding calculated values are... Can be used as the system . It can be set according to the performance requirements of the magnification, and the usual value is 0.7 to 0.95.
[0105] To avoid drastic fluctuations in coating thickness between adjacent cycles, and The value should be chosen such that the single thickness adjustment does not exceed 20% of the current coating thickness. When the model outputs... When the model outputs... At this time, the controller can reduce the slit gap of the coating head, increase the coating speed, reduce the solid content of the slurry, or increase the proportion of pore-forming components. The above actions can be converted into equipment set values by the coating equipment controller based on the model output values.
[0106] To make the dual-response corrected gas production rate It has a clear correspondence with the cell operation correction action, and sets a first gas generation threshold. Second gas production threshold and the third gas production threshold .
[0107] For the 5Ah Prussian blue analogue positive electrode soft-pack sodium-ion battery cell described in this embodiment, under the conditions of 25-45℃ and a charge / discharge voltage range of 2.0-3.95V, the first gas generation threshold is... for mol / s, second gas production threshold for mol / s, third gas production threshold for mol / s.
[0108] Among them, the unit circulation gas production increment For the first The gas molar increment obtained by gas analysis equipment, pressure-volume conversion device, or online gas production monitoring device during a complete charge-discharge cycle; the gas production increment per reference unit cycle. Take the median of the unit cycle gas production increment for five consecutive qualified sampling cycles after the formation of exhaust gas, under the same batch, temperature, expansion rate and voltage window.
[0109] The processor triggers the execution of a correction instruction when any of the following conditions are met: (1) The current cycle unit gas production increment satisfies
[0110] (2) Within three consecutive sampling periods, the dual-response corrected gas production rate satisfies
[0111] The processor adjusts the gas production rate based on the dual response. Determine the amount of voltage reduction for the upper limit of charging within the specified range. The details are as follows: when and or satisfy
[0112] When this occurs, it is determined to be gas-producing zone A, and the upper limit of the charging voltage is lowered by 0.05V; When satisfied
[0113] When this occurs, it is determined to be gas-producing zone B, and the upper limit of the charging voltage is reduced by 0.10V; When satisfied
[0114] When the gas generation zone is identified as C, the upper limit of the charging voltage is reduced by 0.15V.
[0115] The revised upper limit voltage for charging satisfies:
[0116] in, For the revised first Upper limit voltage for cycle charging, in V; The upper limit voltage for charging before correction is expressed in volts (V). For the first The voltage reduction amount corresponding to the cycle, in V.
[0117] For a battery cell with an initial charging upper limit voltage of 3.95V, the corrected charging upper limit voltages corresponding to gas generation ranges A, B, and C are 3.90V, 3.85V, and 3.80V, respectively.
[0118] In addition to lowering the upper limit of the charging voltage, the processor can also simultaneously output one or more operation correction instructions, such as reducing the charging rate, shortening the high voltage holding time, or extending the formation and venting time, so that the diaphragm structure parameter adjustment and cell condition adjustment can jointly participate in the gas expansion control.
[0119] In addition to coating thickness, the model can also output the following process actions: adjust the proportion of metal ion capturing components; adjust the proportion of buffer components; adjust coating density, drying temperature, calendering pressure or heat treatment time; adjust venting time, formation current, holding time or temperature during the formation stage; reduce high voltage dwell time, reduce charging rate, shorten high temperature storage time or output maintenance warnings during the operation stage.
[0120] (3) Methods for obtaining model parameters The rate coefficient, correction coefficient, and weighting coefficient in the model can be obtained through material testing, cell testing, and historical batch data calibration.
[0121] in, and It can be obtained through metal dissolution tests at different voltages. Specifically, the Prussian blue analog cathode is immersed in the corresponding electrolyte, and the changes in Fe, Mn, and Ni ion concentrations are tested under different voltage holding conditions. The results are then obtained by fitting the voltage, temperature, and holding time using equation (5).
[0122] in, , and The results can be obtained through static adsorption and dynamic permeation experiments of Fe, Mn, and Ni ions using a diaphragm functional coating. Fitted by the initial adsorption rate, The actual maximum capture capacity of the membrane functional coating is determined by fitting the release rate after prolonged immersion or high-temperature storage. It is obtained from the saturated adsorption capacity.
[0123] in, This can be obtained through EIS, ionic conductivity, or diffusion tests under different metal trapping conditions. If the decrease in Na ion flux is more significant with increasing metal trapping, then... The value increases.
[0124] in, , It can be obtained through acidic byproduct consumption, pH equivalence test, gas generation test, or negative electrode interface impedance growth test under different buffer component contents.
[0125] in, , The calibration can be achieved through a combination of metal ion penetration experiments, negative electrode metal deposition measurements, and gas generation measurements. When the capture site is highly occupied and the local buffering capacity is insufficient, a significant increase in gas generation will improve the efficiency of the calibration. The value of .
[0126] To enable material testing data to be directly incorporated into the parameter calibration process, this invention uses the crystal water content measured by TGA, the vacancy concentration obtained by XRD refinement, and the residual salt equivalent obtained by ICP detection as material-side correction inputs.
[0127] Among them, water of crystallization content The values represent the mass fraction of water of crystallization in the Prussian blue analog cathode material obtained using a fixed TGA testing procedure, expressed in wt%; and the vacancy concentration. Obtained through XRD refinement Vacancy percentage, in %; residual salt equivalent To obtain the surface sodium salt equivalent in the extract solution after surface salt extraction of positive electrode powder, the sodium content in the extract solution was tested by ICP-OES and converted into mmol / g.
[0128] The residual salt equivalent is calculated using the following formula:
[0129] in, The concentration of Na in the extract as measured by ICP-OES is expressed in mol / L. The volume of the extract is in liters (L). The mass of PBA cathode material used for extraction is in grams. This represents the residual sodium salt content on the surface, expressed in mol / g. It will be converted to mmol / g before being used in subsequent calculations.
[0130] For the same PBA material system, a reference value for the water of crystallization content is set. Reference values for vacancy concentration Reference values for residual salt equivalent The reference values are taken from qualified benchmark batches that have completed metal leaching tests, membrane adsorption tests, and cycle tests within the same material system.
[0131] The effect of water of crystallization content on the metal dissolution rate coefficient The correction factor is calculated using the following formula:
[0132] in, This is a correction factor for the water of crystallization content; and All values are calculated in wt%; This is a projection operator used to limit the correction factor to between 0.70 and 1.60.
[0133] Residual salt equivalent as a factor of metal dissolution rate The correction factor is calculated using the following formula:
[0134] in, This is the residual salt equivalent correction factor; and All values are calculated in mmol / g. This is a projection operator used to avoid excessive fluctuations in the metal dissolution rate coefficient due to residual salt detection errors.
[0135] Corrected metal dissolution rate coefficient based on material testing Calculate using the following formula:
[0136] in, This corresponds to the metal dissolution rate coefficient obtained by the PBA material system in the benchmark batch; The coefficient for metal dissolution rate is corrected for water of crystallization content and residual salt equivalent, and the unit is cm / s.
[0137] The effect of water of crystallization content and residual salt equivalent on voltage sensitivity coefficient The correction is calculated using the following formula:
[0138] in, The voltage sensitivity coefficient corresponding to the PBA material system obtained in the reference batch is expressed in V. -1 ; The voltage sensitivity coefficient is corrected for crystal water content and residual salt equivalent, and the unit is V. -1 .
[0139] When the water of crystallization content is higher than the reference value Increase and All increase; when the residual salt equivalent is higher than the reference value, Increase and The synchronous increase transforms the material properties of high-water-content, high-residue PBA cathodes, which are more prone to metal dissolution and high-voltage side reactions, into calculable parameters in the model.
[0140] Vacancy concentration obtained by XRD refinement Without directly changing the actual adsorption capacity of the prepared membrane The minimum design capture capacity used to determine the PBA cathode system is... The minimum design capture capacity is calculated using the following formula:
[0141] in, The maximum capture capacity of the functional coating of the diaphragm in the baseline batch is expressed in mol / g. This represents the vacancy concentration of the current batch of PBA cathode, in percentages (%). The vacancy concentration of the baseline batch of PBA cathode is expressed in % (%). This represents the minimum design capture capacity corresponding to the current batch of PBA cathodes, expressed in mol / g.
[0142] For every 1% increase in vacancy concentration compared to the reference value in the current batch of PBA cathode, the minimum design capture capacity decreases. Increase the baseline maximum capture capacity 2.5%; when the vacancy concentration is lower than the reference value, the minimum design capture capacity shall be reduced accordingly, but shall not be lower than 2.5%; mol / g.
[0143] The actual maximum capture capacity of the diaphragm functional coating should meet the following requirements:
[0144] when When the processor outputs process suggestions, it may suggest increasing the proportion of metal ion capturing components, increasing the density of functional layers on the positive electrode side, increasing the thickness of functional layers, or replacing the high-adsorption-capacity capturing components. At that time, As the maximum capture capacity in equation (7) Input model.
[0145] In this embodiment, the reference batch parameters for different PBA cathode systems can be selected according to Table 1 below.
[0146] Table 1:
[0147] The above baseline parameters are used for model startup and small-sample correction. For PBA cathodes with lattice water content, vacancy concentration, or residual salt equivalent exceeding the baseline batch range, the processor prioritizes correction according to the above formula; when More than 15 wt%, More than 25% or When the concentration exceeds 0.50 mmol / g, the processor marks the batch as a low-confidence batch and outputs suggestions for retesting, adjusting the cathode material process, or reducing the cell release level. It does not directly use the extrapolated parameters to trigger high-risk operation correction instructions.
[0148] (4) Model running sequence The model runs sequentially according to process stages or sampling cycles. At the start of each new cycle, the processor reads the detection data of the positive electrode material, separator, cell, or module and determines whether the data is within the allowable range. Subsequently, the model calculates the metal dissolution flux, free metal ion concentration in the channels, separator capture amount, metal arrival amount on the negative electrode side, Na ion flux, buffer index, gas generation rate, and separator lifetime index in sequence. Finally, the lifetime index and flux deviation are converted into coating thickness, component ratio, formation parameters, or operating parameters.
[0149] S1, the processor acquires the cell voltage measured by the voltage sensor, current sensor and temperature sensor respectively. Current and temperature It also receives the positive electrode side metal ion concentration input from the offline detection device. Buffer component concentration Inhibit component concentration Coating thickness Porosity, tortuosity, pressure, thickness, EIS impedance, gas analysis results, XRD peak position, TGA weight loss, and water content are among one or more of these parameters.
[0150] S2, the processor calculates the metal dissolution flux on the positive electrode side according to equation (5). The amount of metal ions entering the electrolyte is obtained.
[0151] S3, the processor calculates the concentration of free metal ions in the diaphragm channels according to equation (6). This concentration was then used as input for the recursive calculation of diaphragm trapping sites and the calculation of metal migration on the negative electrode side.
[0152] S4, the processor updates the occupancy of diaphragm capture sites according to equations (7) and (8). Determine the remaining capture capacity of the functional coating.
[0153] S5, the processor calculates the capture site occupancy rate, remaining capture rate, metal ion penetration ratio, and negative electrode side metal ion concentration according to equations (9) to (12). To determine the effect of metal penetration through the diaphragm on the negative electrode side reaction.
[0154] S6, the processor calculates the effective diffusion coefficient of Na ions according to equations (13) and (14). and Na ion flux To determine the effect of functional coatings on ion transport.
[0155] S7, the processor calculates the local buffer index of the membrane near the negative electrode side pores and interface region according to equation (15). To determine the stabilizing ability of the buffer component to the local environment.
[0156] S8, the processor calculates the basic gas production rate according to equations (16) and (17). and dual-response corrected gas production rate To determine the impact of metal deposition and local acid-base environment on gas generation.
[0157] S9, the processor calculates the diaphragm life index according to equation (18). It will then provide a normal, warning, correction, or shutdown judgment according to the set window.
[0158] S10, the processor outputs the next stage coating thickness recommendation, capture component ratio, buffer component ratio, coating parameters, formation parameters, or operating derating parameters according to equation (19). After receiving the processor output signal, the controller converts the corresponding parameters into execution instructions in the coating equipment, formation equipment, capacity testing equipment, or BMS.
[0159] S11, the processor backfills the measured capacity, impedance, pressure, thickness, gas generation, and metal deposition results into the parameter table, and performs segmented corrections on the model coefficients to adapt the model to different PBA cathode systems, hard carbon anode systems, electrolyte systems, and capacity specifications.
[0160] (5) Data quality and anomaly handling When input data is temporarily missing, the model extrapolates the most recent valid value and records the missing data in the output.
[0161] For online voltage, current, temperature, and pressure data, the processor uses the five consecutive valid sample values preceding the current sampling point to form a sliding window, and calculates the mean of the sliding window for each. , , , and standard deviation , , , When a current sampled value simultaneously meets the conditions of deviating from the sliding window mean by more than 3 standard deviations and the change in adjacent sampled points exceeding the corresponding absolute jump threshold, the processor classifies the sampled value as an abnormal jump candidate value; where:
[0162] and
[0163] When this happens, the current voltage data is identified as a candidate value for an abnormal voltage jump.
[0164] and
[0165] When this happens, the current current data is identified as a candidate value for an abnormal current jump; among which, This is the 1C current corresponding to the rated capacity of the battery cell. For a 5Ah battery cell, 0.05C corresponds to 0.25A.
[0166] and
[0167] When this happens, the current temperature data is identified as a candidate value for an abnormal temperature jump.
[0168] and
[0169] At that time, the current pressure data is identified as a candidate value for an abnormal pressure jump. Among them, The average pressure value of the previous sliding window, i.e., the previous sampling point. , is the average of the five consecutive effective pressure samples at the end of the window (i.e., the average of the five effective pressure samples at the end of the window). To the The effective pressure sample values are calculated, including the previous sampling point. ); 5% is the current pressure sampling value. relative to the average pressure of the previous sliding window The relative deviation threshold; The small pressure setting to prevent the reference pressure from approaching zero can be determined based on the minimum effective resolution of the pressure sensor.
[0170] For abnormal jump candidate values, the processor further reads the process setting information from the formation equipment, capacity testing equipment, or BMS. If the abnormal jump candidate value does not correspond to a charge / discharge rate switch, constant current / constant voltage stage switch, charging upper limit voltage adjustment, temperature control setting change, venting operation, or pressure release operation, and the jump only lasts for one sampling cycle, it is determined to be sensor noise or instantaneous acquisition abnormality.
[0171] For sampled values determined to be sensor noise or instantaneous acquisition anomalies, the processor replaces them with the median of adjacent valid sampled values; when small abnormal fluctuations in the same direction occur in two consecutive sampling periods, the average of five consecutive valid sampled values is used for smoothing.
[0172] If an abnormal jump candidate value corresponds to a switch in charge / discharge rate, a switch in constant current / constant voltage stage, an adjustment of the charging upper limit voltage, a change in temperature control setting, a venting operation, or a pressure release operation, or if the jump maintains the same direction of change within three consecutive sampling cycles, the processor determines the jump as a real operating condition change, retains the sampled value, and shortens the update cycle of subsequent state quantities to half of the original update cycle. The 3x standard deviation is used to identify abnormal sampled values that deviate from the normal fluctuation range; the absolute jump threshold is used to avoid misjudging normal, minor fluctuations in the battery as abnormal jumps when the standard deviation is small.
[0173] For offline testing data, the model saves the batch number, testing time, testing item, testing method, and testing equipment number. If multiple similar test values appear in the same batch, the processor prioritizes the test value that is closest to the current process stage and has a valid testing status.
[0174] When two test values are obtained for the same test item in the same batch, the processor calculates the relative deviation using the following formula:
[0175] in, For the first The first detection value and the first The relative deviation between individual test values, expressed in % and These are two test values corresponding to the same batch and the same test item.
[0176] When the same batch of the same test item has three or more test values, the processor calculates the maximum relative deviation according to the following formula:
[0177] in, The maximum relative deviation of multiple test values in the same batch, expressed in % . The maximum value among multiple detection values; It is the minimum value among multiple detection values; It is the arithmetic mean of multiple test values.
[0178] When the relative deviation or maximum relative deviation When the relative deviation is less than 15%, the processor will determine the corresponding detection result as valid data and will prioritize the detection value closest to the current process stage; when the relative deviation is less than 15%, the processor will determine the corresponding detection result as valid data and will prioritize the detection value closest to the current process stage. or maximum relative deviation If the error rate exceeds 15%, the processor will determine the test item as abnormal, output a retest suggestion, and will not directly use the test result for membrane preparation parameter release, model coefficient update or high-risk operation correction instructions.
[0179] For key detection items that directly affect metal leaching flux, dual-response corrected gas generation rate, or membrane life index, such as the concentration of Fe, Mn, and Ni metal ions on the positive electrode side, the membrane metal adsorption capacity, gas generation rate, and water content, the processor will mark the batch of data as low-confidence data when the relative deviation exceeds 15%. Low-confidence data is only used for trend display and is not used to trigger the reduction of the upper limit charging voltage, the adjustment of formation parameters, or the determination of cell release.
[0180] For online data, the model outputs a state value and confidence level for each period. The confidence level is determined by the completeness of the input, the size of the residuals, whether the parameters are extrapolated, and whether the state is out of bounds. Low confidence level results can be included in trend display but do not directly trigger high-risk actions.
[0181] II. Preparation of Dual-Response Membranes Based on the output of the above model This invention prepares a dual-response membrane by considering the density of capture sites, the concentration of buffer components, and the retention rate of Na flux. The membrane can be made of polyethylene, polypropylene, polyethylene / polypropylene composite membranes, nonwoven fabric membranes, or ceramic composite membranes as the base membrane.
[0182] The positive electrode side coating comprises a metal ion capturing component, a local acid-base buffer component, a binder, and a pore-forming component. The metal ion capturing component can be functional particles or polymers containing phosphorus, nitrogen, carboxyl, hydroxyl, or cyano coordination sites, or inorganic porous materials capable of adsorbing metal ions such as Fe, Mn, and Ni. The local acid-base buffer component can be phosphates, borates, carbonates, weak acid-weak base salts, or polymer components with buffering capacity. The binder can be PVDF, PMMA, PAN, CMC, SBR, PAA, or other electrolyte-stabilized bonding systems. The pore-forming component maintains Na ion channels, preventing coating densification that could lead to increased polarization.
[0183] The intermediate Na ion transport layer is the uncoated base film body region retained between the metal ion capture and local buffer functional layer on the positive electrode side and the side reaction suppression layer on the negative electrode side.
[0184] The intermediate Na ion transport layer does not have additional metal ion capturing components, local acid-base buffer components, binders, pore-forming components, or independent ceramic frameworks. Its Na ion transport channels are formed by the continuous microporous structure of the base film itself.
[0185] The intermediate Na ion transport layer is made of polyethylene, polypropylene, or a polyethylene / polypropylene composite film. The thickness of the intermediate Na ion transport layer is 12–16 μm, and the porosity is 40%–48%, with a porosity not less than 40%, to ensure the stability of ion transport between electrolyte wetting, continuous Na ion migration, and the double-sided functional coatings.
[0186] The dry film thickness of the metal ion capture and local buffering functional layer on the positive electrode side is 2.0–3.0 μm; the dry film thickness of the side reaction suppression layer on the negative electrode side is 0.5–1.5 μm. After double-sided coating, the total dry film thickness of the separator is 14.5–20.5 μm, and the thickness of the intermediate Na ion transport layer accounts for 72.7%–86.5% of the total dry film thickness of the separator, preferably 75%–85%.
[0187] The negative electrode side reaction suppression layer is used to reduce the deposition activity of Fe, Mn, or Ni metal ions that pass through the separator on the surface of the hard carbon negative electrode, thereby slowing down abnormal SEI growth and gas generation. The side reaction suppression layer can be one or more of ceramic particles, fluorine-containing interface stabilizing components, flexible polymers, or low-reactivity porous materials.
[0188] During preparation, the positive electrode side coating slurry is uniformly dispersed and coated onto the positive electrode side of the base film. After drying, the coating thickness is controlled between 0.2 and 8 μm. If the model output Na ion flux retention rate is lower than the set value, the solid content is reduced, the pore ratio is increased, the coating thickness is reduced, or the coating particle size is adjusted. If the model output metal capture rate is lower than the set value, the capture component ratio is increased, the coating areal density is increased, or the thickness of the positive electrode side functional coating is increased. If the model output gas production reduction rate is insufficient, the buffer component ratio is increased or a negative electrode side side side reaction suppression layer is added.
[0189] The resulting diaphragm undergoes tests for thickness, porosity, gas permeability, liquid absorption rate, thermal shrinkage, EIS impedance, metal ion adsorption capacity, and cell gas generation before being assembled into the cell. The assembled Prussian blue analogue cathode sodium-ion cell can continue to be used during formation, capacity testing, cycling, storage, or module operation phases, and the measured pressure, thickness, gas, impedance, and capacity data are re-entered into the parameter table for correction. , , , , , , , , , , , , Parameters such as these.
[0190] Example 1
[0191] This embodiment uses a manganese-iron-based Prussian blue analog cathode, a hard carbon anode, and a NaPF6-based carbonate electrolyte to assemble a 5Ah soft-pack sodium-ion battery cell, which is used to verify the role of a dual-response membrane for metal dissolution and gas generation in inhibiting metal ion penetration, reducing anode side reactions, and mitigating soft-pack gas expansion.
[0192] The positive electrode active material uses a manganese-iron-based Prussian blue analogue. The positive electrode sheet consists of active material, conductive agent, and binder in a mass ratio of 92:4:4. The negative electrode active material uses hard carbon. The negative electrode sheet consists of hard carbon, conductive agent, and binder in a mass ratio of 94:2:4. The electrolyte uses a 1 mol / L NaPF6 carbonate system. The soft-pack cell is designed with a capacity of 5 Ah, and the effective positive electrode area is approximately 260 to 300 cm². 2 The injection volume is controlled within the allowable range of conventional soft packaging processes.
[0193] The separator uses a polyolefin-based membrane as the substrate. The main region of the substrate membrane, namely the intermediate Na ion transport layer, has a thickness of 12–16 μm and a porosity of 40%–48%. The intermediate Na ion transport layer does not incorporate additional binders, metal ion capturing components, local acid-base buffering components, pore-forming components, or an independent ceramic framework; its continuous micropores directly serve as electrolyte wetting channels and Na ion transport channels. A metal ion capturing and local buffering functional layer is formed on the side of the intermediate Na ion transport layer near the positive electrode, with a dry film thickness of 2.0–3.0 μm, preferably 2.5 μm. A side reaction suppression layer is formed on the side of the intermediate Na ion transport layer near the negative electrode, with a thickness of 0.5–1.5 μm. After double-sided coating, the total dry film thickness of the separator is 14.5–20.5 μm, and the thickness of the intermediate Na ion transport layer accounts for 72.7%–86.5% of the total dry film thickness.
[0194] In this embodiment, the positive electrode side metal ion capture and local buffering functional layer is composed of amino-functionalized mesoporous silica, nano-magnesium phosphate, battery-grade polyvinylidene fluoride binder, and mesoporous alumina pore-forming components.
[0195] The metal ion capturing component is amino-functionalized mesoporous silica, denoted as NH2-mSiO2. The NH2-mSiO2 has an average particle size of 100–300 nm and a specific surface area of 200–500 m². 2 The surface amino content is 0.5–1.5 mmol / g. The amino coordination sites and mesoporous structure in amino-functionalized mesoporous silica are used to adsorb or complex Fe, Mn, and Ni metal ions, reducing the free concentration of metal ions in the membrane channels.
[0196] The local acid-base buffer component is selected from nano-magnesium phosphate, with the chemical formula Mg3(PO4)2 and an average particle size of 50–150 nm. Nano-magnesium phosphate is used to alleviate local acid-base drift induced by electrolyte decomposition products, HF byproducts, or metal ion deposition near the membrane pores and negative electrode interface, and to reduce the probability of side reactions continuing.
[0197] The binder used is battery-grade polyvinylidene fluoride, denoted as PVDF, with a weight-average molecular weight of [missing information]. ~ In this embodiment, the preferred weight-average molecular weight is approximately [value missing]. The PVDF is used to stably bond amino-functionalized mesoporous silica, nano-magnesium phosphate, and mesoporous alumina to the positive electrode side surface of a polyolefin-based membrane.
[0198] The pore-forming component is mesoporous alumina particles, denoted as m-Al2O3, with an average particle size of 100–250 nm and a specific surface area of 80–200 m². 2 / g. Mesoporous alumina particles are dispersed in the functional coating to form continuous channels between particles, maintain electrolyte wetting ability and Na ion migration channels, and prevent the functional layer from becoming dense due to excessive introduction of trapping and buffering components.
[0199] The solid components of the positive electrode side functional coating, by mass parts, have the following mass ratios: amino-functionalized mesoporous silica, nano-magnesium phosphate, PVDF, and mesoporous alumina:
[0200] The positive electrode side functional coating slurry uses battery-grade N-methylpyrrolidone as a solvent, denoted as NMP, and the solid content of the slurry is controlled at 12-15 wt%, preferably 13 wt% in this embodiment.
[0201] Taking the preparation of 100g of positive electrode side functional coating slurry as an example, first weigh 1.95g of PVDF and add it to 87.00g of battery-grade NMP. Stir at 40-50℃ for 1-2 hours to fully dissolve the PVDF and obtain a binder solution. Then add 5.85g of amino-functionalized mesoporous silica, 2.60g of nano-magnesium phosphate and 2.60g of mesoporous alumina to the binder solution.
[0202] The resulting mixed slurry was subjected to high-speed dispersion and ultrasonic treatment, wherein the high-speed dispersion speed was 800-1200 r / min and the time was 30-60 min; the ultrasonic dispersion time was 10-20 min. After dispersion, the slurry was allowed to stand under vacuum for 10-30 min to degas, resulting in a positive electrode side functional coating slurry with a solid content of 13 wt%.
[0203] The slurry is coated onto the side of the polyolefin-based film near the positive electrode using slot coating, microgravure coating, or blade coating. After coating, it is first dried at 60–70°C for 5–15 min, and then dried under vacuum at 70–80°C for 2–4 h to remove residual NMP and moisture. After drying, the dry film thickness of the metal ion trapping and local buffering functional layer on the positive electrode side is controlled to be 2.0–3.0 μm, preferably 2.5 μm.
[0204] In the above formulation, the mass ratio of amino-functionalized mesoporous silica, nano-magnesium phosphate, PVDF, and mesoporous alumina can be adjusted within the following range:
[0205] When the metal capture rate calculated by the model is lower than the set value, increase the proportion of amino-functionalized mesoporous silica to 50-55 parts; when the gas production reduction rate calculated by the model is lower than the set value, increase the proportion of nano-magnesium phosphate to 25-30 parts; when the Na ion flux retention rate is lower than the set value, reduce the proportion of PVDF to 10-15 parts, or increase the proportion of mesoporous alumina to 25-30 parts.
[0206] In this embodiment, the dry film thickness of the functional layer on the positive electrode side is controlled between 2.0 and 3.0 μm, preferably around 2.5 μm; the thickness of the side reaction suppression layer on the negative electrode side is controlled between 0.5 and 1.5 μm; and the total thickness of the separator after double-sided coating is controlled within the allowable range for conventional soft-pack cell assembly. After coating, it is dried at 60 to 80°C, and then residual solvent and moisture are further removed under vacuum conditions.
[0207] In this embodiment, the positive electrode side metal ion capture and local buffering functional layer is formed on the positive electrode side surface of the polyolefin base film using a slit extrusion coating method. Before coating, the base film is placed in a dry environment with a dew point not higher than -30°C for at least 30 minutes for equilibration treatment to reduce the impact of adsorbed water on the base film surface on the wettability of the slurry and the subsequent electrolyte injection performance of the battery cell.
[0208] During the coating process, the slit gap between the slit coating head outlet and the base film surface is controlled at 80–120 μm, preferably 100 μm; the base film running speed is controlled at 0.3–0.8 m / min, preferably 0.5 m / min. The feed flow rate is adjusted according to the slurry solid content, coating speed, and target dry film thickness to control the wet film thickness of the positive electrode side functional layer at 45–65 μm, and the dry film thickness after drying at 2.0–3.0 μm, preferably 2.5 μm.
[0209] After the functional layer on the positive electrode side is dried and its thickness is measured, the separator is flipped over, and a side reaction suppression layer is formed on the negative electrode side of the base film using the same slit extrusion coating method. The slit gap of the negative electrode side side side side reaction suppression layer is controlled to be 60–100 μm, the base film running speed is controlled to be 0.4–1.0 m / min, and the thickness of the dried side reaction suppression layer is controlled to be 0.5–1.5 μm, preferably 1.0 μm.
[0210] After double-sided coating, the total dry membrane thickness of the diaphragm is controlled to be 14.5–20.5 μm. Among them, the middle Na ion transport layer is the uncoated base membrane main body area with a thickness of 12–16 μm, ensuring that continuous Na ion migration channels are still maintained between the double-sided functional coatings.
[0211] The coating and primary drying processes are carried out under a dry nitrogen atmosphere, with the nitrogen dew point not exceeding -30°C, preferably not exceeding -40°C, to reduce the risk of moisture entering the membrane pores, buffer components, and functional particles. After the positive electrode functional layer and the negative electrode side reaction inhibition layer are coated, they are first dried under a dry nitrogen atmosphere at 60–70°C for 5–15 minutes; then, a secondary vacuum drying is carried out at 65–80°C under a vacuum of -0.08 to -0.095 MPa for 2–4 hours to remove residual NMP and adsorbed water.
[0212] After vacuum drying, the diaphragm is cooled to room temperature in a dry environment with a dew point not higher than -30°C, and then sealed and transferred to the cell assembly process.
[0213] After cell assembly, formation and testing were performed according to the following procedure: First, low-current formation was conducted at 25℃ with a current of 0.05C to 0.1C, followed by venting and encapsulation. Then, a cycle test was conducted at 45℃, with a charge / discharge voltage range of 2.0 to 3.95V, a rate of 1C, and 500 cycles. During the test, capacity, coulombic efficiency, DC internal resistance, EIS impedance, pouch thickness variation, and cell appearance were recorded. After cycling, the cell was disassembled, and ICP-OES analysis was performed on the positive electrode separator, the middle of the separator, the negative electrode separator, and the hard carbon negative electrode to determine the content of metal elements such as Mn, Fe, and Ni. Simultaneously, gas analysis methods were used to detect the content of CO2, CO, H2, and hydrocarbon gases.
[0214] Calculation and determination process in Example 1 During the cycle, the processor receives voltage, current, temperature, cycle time, and offline detection input of the positive electrode side metal ion concentration. When Mn ions are the primary monitoring target, the Mn ion concentration on the positive electrode side is within a certain range after electrolyte sampling and ICP-OES detection. The concentration is on the order of mol / L. The processor calculates the metal dissolution flux on the positive electrode side based on the metal ion concentration on the positive electrode side, the cell voltage, and the concentration of the suppressing component in the electrolyte.
[0215] After calculating the metal leaching flux on the positive electrode side, the concentration of free metal ions within the membrane pores is further calculated by combining the effective volume of the membrane channels, the effective contact area between the positive electrode and the membrane, the sampling period, and the capture amount of the functional coating. This concentration is not a directly set value, but is determined by the amount of metal ions entering the channels from the positive electrode side, the amount of residual metal ions in the channels from the previous period, and the newly captured amount in the current period.
[0216] In the early stages of cycling, the functional layer has ample capture sites, resulting in a low concentration of free metal ions within the membrane channels and minimal metal deposition on the negative electrode side. As cycling progresses, capture sites gradually become occupied, increasing the capture site occupancy rate and decreasing the remaining capture rate. The processor calculates the metal ion penetration ratio based on the capture site occupancy rate and the remaining capture rate, thereby assessing the risk of metal accumulation on the negative electrode side.
[0217] In this embodiment, the occupancy rate of the capture sites entered a relatively high range in the later stages of cycling, but it had not yet reached complete saturation. Due to the continuous capture of metal ions by the functional layer on the positive electrode side, the metal deposition on the negative electrode side was significantly lower than that of the ordinary membrane group. After disassembly, the Mn content detected on the hard carbon negative electrode side was lower than that of the ordinary membrane group, indicating that the migration of metal ions across the membrane was inhibited.
[0218] Simultaneously, the processor calculates the effective diffusion coefficient of Na ions based on the membrane porosity, tortuosity, and trapping site occupancy rate, and further calculates the Na ion flux retention rate. In this embodiment, the dual-response membrane maintains a high Na ion flux even after the introduction of the functional coating, and the rate performance and polarization growth after cycling are within acceptable ranges. This result indicates that the functional layer on the positive electrode side did not cause severe transport blockage due to excessive thickness or density.
[0219] The processor also calculates the local buffer index of the membrane near the negative electrode side pores and interface region based on the effective concentration of the buffer component and the equivalent concentration of acidic byproducts. When the capture site occupancy rate increases and the local buffer index decreases, the processor determines whether the gas generation amplification condition is triggered. If the capture site occupancy rate reaches or exceeds 0.7 and the local buffer index is less than or equal to 0.3, the gas generation amplification factor is included in the calculation; if the above conditions are not met, the gas generation amplification factor is taken as 0.
[0220] In this embodiment, some test points in the later stages of cycling meet the dual threshold judgment condition. Based on this, the processor outputs operational correction suggestions, including shortening the high-voltage holding time, reducing the upper charging voltage limit by 0.05 to 0.10V, extending the formation venting time, or appropriately reducing the high-temperature cycling rate. For the next batch of separator fabrication, the processor outputs fabrication correction suggestions including increasing the thickness of the positive electrode side functional layer from approximately 2.5 μm to approximately 2.8 μm, increasing the proportion of metal trapping components, and slightly increasing the proportion of buffer components, while maintaining the proportion of pore-forming components to avoid a significant decrease in Na ion flux.
[0221] Detection results of Example 1
[0222] After 500 cycles, the pouch cell using the dual-response diaphragm of this embodiment performs as follows: The amount of Mn deposited on the negative electrode side was significantly lower than that of the ordinary membrane group, and the metal arrival rate on the negative electrode side was about one-fifth to one-third of that of the ordinary membrane group. The gas production per unit cycle of the battery cell is lower than that of ordinary diaphragm groups and single-function coated diaphragm groups; The thickness increase of the soft pack is controlled within approximately 3%; EIS interfacial impedance growth is lower than that of ordinary diaphragm groups; After 500 cycles, the capacity retention rate remained in the range of approximately 88% to 91%. The Na ion flux retention rate remains above approximately 90%.
[0223] The results indicate that the combined effects of positive electrode metal capture, local buffering, and negative electrode side reaction suppression can reduce metal ion penetration, negative electrode side reactions, and gas generation, while maintaining good Na ion transport capacity.
[0224] Comparative Example 1: Ordinary polyolefin membrane Comparative Example 1 used an unmodified polyolefin membrane. The membrane thickness, porosity, and matrix material were the same as the base membrane in Example 1, but the metal ion capture layer, local buffer layer, and negative electrode side reaction suppression layer were not provided. The positive electrode material, negative electrode material, electrolyte, injection volume, formation program, cycling temperature, voltage range, and rate were all the same as in Example 1.
[0225] Under cycling conditions of 45°C, 2.0 to 3.95V, and 1C, after metal ions such as Mn and Fe dissolved from the positive electrode side of the PBA enter the electrolyte, the ordinary membrane only provides physical isolation and ion transport channels, and cannot effectively capture the metal ions. In the later stages of cycling, some metal ions pass through the membrane and deposit on the surface of the hard carbon negative electrode.
[0226] After 500 cycles, the cell was disassembled and the hard carbon negative electrode was subjected to ICP-OES testing. The Mn content on the negative electrode side was significantly higher than that in Example 1. Combined with the conversion of the dissolution amount on the positive electrode side, the metal arrival rate on the negative electrode side of the ordinary diaphragm group was at a high level, typically exceeding 30%. Due to the greater metal deposition on the negative electrode surface, electrolyte reduction and decomposition and abnormal SEI growth were more pronounced, and EIS testing showed a faster increase in interfacial impedance.
[0227] Thickness testing showed a significant increase in the thickness of the soft pack in the conventional diaphragm group, with an increase of approximately 6% to 8% after 500 cycles. Gas analysis results showed that the contents of CO2, CO, and a small amount of H2 were all higher than in Example 1. Capacity testing showed that the capacity retention rate of the conventional diaphragm group after 500 cycles was generally lower than that of Example 1, ranging from approximately 75% to 80%.
[0228] Comparative Example 1 shows that although ordinary polyolefin membranes have good Na ion transport capabilities, they are unable to handle the problem of PBA positive electrode metal migrating to the negative electrode side after dissolution, and they are also unable to suppress negative electrode side reactions and soft pack gas expansion caused by metal deposition.
[0229] Comparative Example 2: Single Metal-Capturing Coated Separator Comparative Example 2 uses a single metal ion trapping coating separator. This separator has a metal ion trapping coating on the positive electrode side, with a coating thickness similar to the positive electrode side functional layer in Example 1, approximately 2.5 μm; however, this separator does not have a local acid-base buffer component, nor does it have a negative electrode side side side reaction suppression layer. The cell material system, electrolyte injection volume, formation process, cycling temperature, voltage range, and rate capability are all the same as in Example 1.
[0230] In the early stages of cycling, the single-metal trapping coating can adsorb or complex some metal ions such as Mn, Fe, and Ni, resulting in a lower metal deposition on the negative electrode side compared to conventional membrane groups. As cycling progresses, the trapping sites are gradually occupied, the remaining trapping capacity decreases, and the concentration of free metal ions within the membrane channels gradually increases. Due to the lack of local acid-base buffer components, acidic byproducts near the negative electrode channel and interface cannot be stabilized in a timely manner, and electrolyte side reactions continue to occur.
[0231] After 500 cycles, disassembly and testing showed that the metal deposition on the negative electrode side of Comparative Example 2 was lower than that of the conventional diaphragm group, but higher than that of Example 1. The metal arrival rate on the negative electrode side was typically around 20%. Due to the absence of a local buffer layer and a negative electrode side reaction suppression layer, the gas production per unit cycle of Comparative Example 2 remained high, with the pouch thickness increasing by approximately 5% to 6%. EIS testing showed that the increase in interfacial impedance was lower than that of the conventional diaphragm group, but significantly higher than that of Example 1. The capacity retention rate was generally in the range of approximately 81% to 84%.
[0232] Comparative Example 2 illustrates that a single metal trapping layer can reduce metal ion penetration, but when the buffering capacity is insufficient, side reactions and gas generation at the negative electrode side interface are still difficult to fully suppress. Relying solely on the trapping layer to improve metal interception capability cannot completely solve the gas expansion problem of PBA positive electrode soft-pack cells.
[0233] Comparative Example 3: Single Acid-Base Buffer Coated Separator Comparative Example 3 uses a single acid-base buffer coating membrane. This membrane contains a local buffer component, with a coating thickness of approximately 2.5 μm, but does not contain a metal ion capturing component or a negative electrode side reaction suppression layer. The cell material system, electrolyte injection volume, formation process, cycling temperature, voltage range, and rate capability are all the same as in Example 1.
[0234] During cycling, the single buffer coating can reduce acid-base drift near the membrane channels and the negative electrode interface, mitigating some electrolyte decomposition side reactions. Gas analysis results show that the gas production of Comparative Example 3 is lower than that of the ordinary membrane group. However, due to the lack of metal ion trapping sites, metal ions such as Mn and Fe dissolved from the positive electrode side can still easily pass through the membrane and reach the surface of the hard carbon negative electrode.
[0235] After 500 cycles, ICP-OES analysis showed that the metal deposition on the negative electrode side of Comparative Example 3 was lower than that of the conventional diaphragm group but significantly higher than that of Example 1. The metal reach on the negative electrode side was typically around 30%. The pouch thickness increased by approximately 4% to 5%, lower than that of the conventional diaphragm group and the single metal trapping group, but still higher than that of Example 1. EIS testing showed that the increase in interfacial impedance was somewhat mitigated, but due to the continued presence of metal deposition, the impedance increase was still significant. The capacity retention was generally in the range of approximately 83% to 85%.
[0236] Comparative Example 3 illustrates that a single acid-base buffer layer can reduce some of the gas generation caused by local acid-base drift, but it cannot sufficiently prevent metal ions from migrating to the negative electrode side. For PBA positive electrode pouch cells, relying solely on a buffer layer is insufficient to simultaneously control metal deposition and long-term impedance growth.
[0237] Comparative Example 4: Bifunctional diaphragm without a negative electrode side reaction inhibition layer Comparative Example 4 employs a dual-functional coating for metal trapping and localized buffering on the positive electrode side, but omits the negative electrode side side reaction suppression layer. This design is used to differentiate the role of the negative electrode side side reaction suppression layer in later cycles. The remaining positive electrode material, negative electrode material, electrolyte, separator base film, formation process, and cycling conditions are consistent with Example 1.
[0238] This approach effectively reduces metal ion penetration during the early stages of cycling and mitigates acid-base drift near the membrane pores, resulting in lower capacity decay and gas production compared to conventional membrane systems. However, in the later stages of cycling, a small amount of metal ions still penetrates the membrane and reaches the hard carbon anode surface. Since no side reaction suppression layer is present on the anode side, these metal ions may still become electrolyte decomposition active sites on the anode surface, leading to continued SEI thickening.
[0239] After 500 cycles, the metal reach on the negative electrode side of Comparative Example 4 was lower than that of Comparative Examples 2 and 3, but the increase in pouch thickness was still higher than that of Example 1. Its capacity retention was generally in the range of approximately 86% to 88%, which was better than that of the single-function separator, but slightly lower than that of Example 1. This comparative example illustrates that the bifunctional layer on the positive electrode side can significantly reduce risk, but the side reaction suppression layer on the negative electrode side has a complementary effect in further reducing gas generation and impedance growth.
[0240] Comparison of Examples and Comparative Examples The test results of each embodiment and the comparative example are compared in Table 2 below. Table 2:
[0241] The results show that although Comparative Example 1 has good basic ion transport capability, it cannot effectively suppress metal ion penetration and negative electrode gas generation; Comparative Example 2 can reduce metal ion penetration, but it is not good at controlling local acid-base drift and side reaction gas generation; Comparative Example 3 can alleviate acid-base drift, but it cannot sufficiently reduce metal ion deposition; Comparative Example 4 has dual-function protection on the positive electrode side, but it lacks a negative electrode side side reaction suppression layer, and there is still a certain risk of gas expansion in later cycles; Example 1 simultaneously sets a positive electrode side metal capture and local buffering functional layer, an intermediate Na ion transport layer, and a negative electrode side side reaction suppression layer, so it can reduce metal penetration, gas generation, and thickness growth while maintaining Na ion flux.
[0242] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a Prussian blue positive electrode dual-response membrane, characterized in that, Includes the following steps: Collect material testing data, membrane structure data, cell operation data, and process equipment data for Prussian blue analogue cathode sodium ion cells. The data includes one or more of the following: cell voltage, current, temperature, positive electrode side metal ion concentration, membrane buffer component concentration, electrolyte inhibition component concentration, membrane functional coating thickness, porosity, tortuosity, pressure, thickness, impedance, and gas analysis results. The membrane state parameters are constructed, including the amount of metal ions captured in the functional layer on the positive electrode side of the membrane, the concentration of metal ions on the negative electrode side, the effective flux of Na ions through the membrane, the local buffer index of the membrane near the negative electrode side pores and interface region, and the membrane lifetime index. The metal leaching flux on the positive electrode side is calculated based on the concentration of metal ions on the positive electrode side, the cell voltage, and the concentration of the suppressing component in the electrolyte. The concentration of free metal ions in the membrane channels is calculated based on the metal dissolution flux on the positive electrode side, the effective volume of the membrane channels, and the membrane capture capacity. The metal ion capture capacity of the diaphragm is updated based on the concentration of free metal ions in the pores of the diaphragm, the maximum capture capacity, the adsorption rate coefficient, and the desorption rate coefficient. The capture site occupancy rate, remaining capture rate, and metal ion penetration ratio are calculated based on the metal ion capture amount and maximum capture capacity of the diaphragm, and the metal ion concentration on the negative electrode side is updated accordingly. The effective diffusion coefficient of Na ions was calculated based on the occupancy rate of the capture sites, the porosity of the membrane, and the tortuosity, and the effective flux of Na ions through the membrane was further calculated. The local buffer index is calculated based on the concentration of the buffer component and the equivalent concentration of the acidic byproduct, and the basic gas production rate is calculated based on the concentration of metal ions on the negative electrode side, the concentration of reactive components in the electrolyte, and the temperature. When the capture site occupancy rate and the local buffer index meet the preset dual threshold conditions, the basic gas production rate is amplified and corrected to obtain the dual-response corrected gas production rate. The membrane lifetime index is calculated based on the remaining capture rate, effective Na ion flux, and dual-response corrected gas generation rate. The membrane functional coating thickness, capture component ratio, buffer component ratio, coating parameters, formation parameters, or cell operating parameters are output based on the membrane lifetime index and Na ion flux retention rate. Prepare or adjust a dual-response membrane according to the output results. The dual-response membrane includes a metal ion capture and local buffering functional layer on the positive electrode side, an intermediate Na ion transport layer, and a side reaction suppression layer on the negative electrode side.
2. The method according to claim 1, characterized in that, The diaphragm state quantity is written as: in, This represents the diaphragm state vector during the k-th sampling period or process stage. This represents the amount of metal ions captured in the functional layer on the positive electrode side of the separator. The concentration of metal ions reaching the negative electrode side; This represents the effective flux of Na ions through the membrane. The local buffering index of the diaphragm near the negative electrode side pores and interface region; This refers to the diaphragm life index. The membrane state variables are updated periodically in the order of positive electrode dissolution, pore free metal accumulation, membrane capture, negative electrode side metal arrival, Na ion transport, local buffering, gas generation correction, and lifetime determination. Each state variable is derived recursively from the current input and the state variable of the previous cycle.
3. The method according to claim 1, characterized in that, The metal leaching flux on the positive electrode side is calculated using the following formula: in, The dissolution flux of metal ions from the positive electrode side into the electrolyte during the k-th period; This is the metal dissolution rate coefficient; The concentration of soluble metal ions on the positive electrode side; Voltage sensitivity coefficient; This represents the cell voltage or positive electrode relative reference potential in the kth cycle. Reference voltage; The coefficient representing the influence of the inhibitory component or complexing component on metal dissolution; The concentration of effective components in the electrolyte that can participate in inhibiting metal dissolution or stabilizing complexation; When the inhibitory component in the electrolyte and the buffering component in the membrane come from the same buffer or complexing material, the conversion is performed according to the following formula: in, The effective proportion of buffer or complexing components entering the electrolyte and participating in the dissolution inhibition effect on the positive electrode side, with a value ranging from 0 to 1; This refers to the effective concentration of the buffer component in the diaphragm functional coating.
4. The method according to claim 1, characterized in that, The concentration of free metal ions within the membrane channels is calculated using the following formula: in, The concentration of free metal ions in the positive electrode side channel of the diaphragm during the kth period; For projection operators; This represents the upper limit of the metal ion concentration within the diaphragm pores. This represents the concentration of free metal ions within the diaphragm pores in the previous cycle. This refers to the effective electrolyte volume within the diaphragm pores. This represents the metal leaching flux; This represents the effective contact area between the positive electrode and the diaphragm. This refers to the sampling period or process stage time. For the quality of the diaphragm functional coating; and These represent the metal capture amounts for the current period and the previous period, respectively. The projection operator is used to limit the calculated values of the model to a physical range that is measurable, manufacturable, or operable for Prussian blue analog sodium-ion batteries. The upper and lower limits are determined by the failure boundary of the same system battery, the equipment processing capability, and the safe operating window.
5. The method according to claim 1, characterized in that, The membrane metal ion capture capacity is updated using the following formula: in, For the diaphragm capture amount in the next cycle; This represents the current cycle diaphragm capture amount. Maximum capture capacity; The adsorption rate coefficient of metal ions; This represents the concentration of free metal ions within the membrane pores. This is the desorption or deactivation rate coefficient; When Fe, Mn, and Ni metal ions are present simultaneously in the Prussian blue analog cathode, the and Labeled separately according to the type of metal, and weighted according to the concentration ratio of each metal ion in the membrane channels: in, Indicates Fe, Mn, or Ni; Let be the molar proportion of the i-th type of metal ion in the total amount of free metal ions within the membrane channel, and its value ranges from 0 to 1, and satisfies the following conditions: ; and , respectively, are the adsorption rate coefficient and desorption rate coefficient of the i-th type of metal ion.
6. The method according to claim 1, characterized in that, The capture site occupancy rate, remaining capture rate, metal ion penetration ratio, and negative electrode side metal ion concentration are calculated using the following formulas: in, The occupancy rate of the diaphragm capture sites in the kth cycle; The remaining capture rate of the diaphragm in the k-th cycle; The penetration ratio of metal ions in the kth period; The remaining capture capacity has a suppressive effect on metal penetration. This represents the concentration of metal ions on the negative electrode side in the next cycle. This represents the concentration of metal ions on the negative electrode side during the current cycle. This represents the upper limit of metal concentration on the negative electrode side. This is a correction factor for transmembrane migration; This is the effective volume of the electrolyte; It represents the rate coefficient for metal deposition, consumption, or fixation on the negative electrode side.
7. The method according to claim 1, characterized in that, The effective diffusion coefficient and effective flux of Na ions are calculated using the following formulas: in, The effective diffusion coefficient of Na ions in the kth period; The reference diffusion coefficient; The porosity of the diaphragm; Porosity index; The degree of diaphragm tortuosity; The coefficient representing the influence of capture site occupancy on Na ion transport resistance; This refers to the occupancy rate of the septum capture sites. This represents the effective flux of Na ions through the membrane. The difference in Na ion concentration across the membrane; For the effective transmission thickness of the diaphragm; The transference number of the Na ion; Let be the current in the k-th period; It is Faraday's constant; The effective area of the electrode; in, Used to calculate the additional effects of metal ion trapping on the effective cross-sectional area of the pores and the Na ion transport path.
8. The method according to claim 1, characterized in that, The local buffer index, the basic gas production rate, and the dual-response corrected gas production rate are calculated using the following formulas: in, The local buffering index of the diaphragm near the negative electrode side pores and interface region; This is the steepness coefficient for buffer response; This represents the effective concentration of the buffer component. It refers to the equivalent concentration of acidic byproducts, HF-type byproducts, or localized acidity. The rate of formation of basic gases; This is the rate coefficient for gas production reaction; The concentration of reactive components in the electrolyte; This is the apparent activation energy of the gas-producing reaction; It is the gas constant; The temperature of the k-th period; The gas generation rate is the corrected rate after the dual response. The remaining capture capacity has a suppressive effect on gas production. The local buffering capacity has a suppressive effect on gas production. The gas generation amplification factor is the result of the combined effects of high site occupancy and insufficient buffering. Among them, the A dual-threshold triggering rule is adopted, when the capture site occupancy rate or local buffer index At that time, take ;when and hour, Take the value according to the calibration value.
9. The method according to claim 1, characterized in that, In the dual-response membrane, the solid components of the positive electrode side metal ion capture and local buffering functional layer are as follows by mass: 45 parts of amino-functionalized mesoporous silica, 20 parts of nano-magnesium phosphate, 15 parts of polyvinylidene fluoride, and 20 parts of mesoporous alumina. The amino-functionalized mesoporous silica has an average particle size of 100–300 nm and a specific surface area of 200–500 m². 2 / g, with a surface amino content of 0.5–1.5 mmol / g; The average particle size of the nano-magnesium phosphate is 50–150 nm. The membrane life index and the recommended coating thickness for the next stage are calculated using the following formulas: in, This refers to the diaphragm life index. , , These are the weighting coefficients for the remaining capture rate, Na ion flux, and gas production inhibition, respectively, and they satisfy the following conditions: ; This represents the initial Na ion flux or the Na ion flux of the control membrane. The reference gas production rate is for a normal diaphragm or in its initial state. Recommended coating thickness for the next stage; This represents the current coating thickness. and These are the minimum and maximum functional coating thicknesses, respectively. Increase the step size factor for thicknesses when the life index is insufficient; This is the thickness correction coefficient when the Na ion flux is insufficient. This is the lower limit of the diaphragm life index; This represents the lower limit of Na ion flux retention rate. The Na ion flux retention rate; when When the controller increases the slit gap of the coating head, decreases the coating speed, increases the solid content of the slurry, or increases the coating amount per unit area; when At the same time, the controller reduces the slit gap of the coating head, increases the coating speed, reduces the solid content of the slurry, or increases the proportion of pore-forming components; When the measured unit cycle gas production increment of the battery cell Exceeding the benchmark unit cycle gas production increment 5%, or the dual-response corrected gas production rate over three consecutive sampling periods. All are not lower than the first gas production threshold. At that time, the processor sends an operation correction command to the formation device, capacity grading device, or BMS; among them, for a 5Ah Prussian blue analog cathode soft-pack sodium-ion battery cell, the first gas generation threshold is... for mol / s, second gas production threshold for mol / s, third gas production threshold for mol / s; When the unit cycle gas production increment exceeds 5% of the baseline unit cycle gas production increment and the dual-response corrected gas production rate Less than the first gas production threshold , or when When the processor lowers the charging voltage limit by 0.05V, the processor will lower the charging voltage limit by 0.05V. When the processor lowers the charging voltage limit by 0.10V, the processor will lower the charging voltage limit by 0.10V. When this occurs, the processor will lower the upper limit of the charging voltage by 0.15V; the operation correction instruction also includes one or more of the following: reducing the charging rate, shortening the high voltage holding time, or extending the formation and exhaust time.
10. A dual-response diaphragm preparation and control system for performing the method according to any one of claims 1 to 9, characterized in that: It includes a data acquisition module, a status calculation module, a parameter output module, an execution control module, and a parameter backfilling module; The data acquisition module is used to collect one or more of the following: cell voltage, current, temperature, positive electrode side metal ion concentration, buffer component concentration, inhibitory component concentration, separator coating thickness, porosity, tortuosity, pressure, thickness, impedance, and gas analysis results. The state calculation module is used to calculate the positive electrode side metal dissolution flux, free metal ion concentration in the membrane channel, membrane capture amount, capture site occupancy rate, remaining capture rate, metal ion penetration ratio, negative electrode side metal ion concentration, Na ion effective diffusion coefficient, Na ion effective flux, local buffer index, basic gas production rate, dual-response corrected gas production rate and membrane lifetime index. The parameter output module is used to output the membrane functional coating thickness, capture component ratio, buffer component ratio, coating parameters, formation parameters, or cell operating parameters based on the membrane lifetime index and Na ion flux retention rate. The execution control module is used to control the coating equipment, drying equipment, calendering equipment, chemical formation equipment, capacity separation equipment, or BMS to perform corresponding actions based on the output results of the parameter output module; The parameter backfilling module is used to backfill the measured capacity, impedance, pressure, thickness, gas generation, and metal deposition results into the parameter table, and to correct the model parameters.